Cotransplantation With Adipose Tissue–derived Stem Cells Improves Engraftment of Transplanted Hepatocytes. Issue 10 (11th April 2022) - Yamana, Hiroki; Inagaki, Akiko; Imura, Takehiro; Nakamura, Yasuhiro; Nishimaki, Hiroyasu; Katano, Takumi; Ohashi, Kazuo; Miyagi, Shigehito; Kamei, Takashi; Unno, Michiaki; Goto, Masafumi
Abstract : Background: Hepatocyte transplantation is expected to be an alternative therapy to liver transplantation; however, poor engraftment is a severe obstacle to be overcome. The adipose tissue–derived stem cells (ADSCs) are known to improve engraftment of transplanted pancreatic islets, which have many similarities to the hepatocytes. Therefore, we examined the effects and underlying mechanisms of ADSC cotransplantation on hepatocyte engraftment. Methods: Hepatocytes and ADSCs were cotransplanted into the renal subcapsular space and livers of syngeneic analbuminemic rats, and the serum albumin level was quantified to evaluate engraftment. Immunohistochemical staining and fluorescent staining to trace transplanted cells in the liver were also performed. To investigate the mechanisms, cocultured supernatants were analyzed by a multiplex assay and inhibition test using neutralizing antibodies for target factors. Results: Hepatocyte engraftment at both transplant sites was significantly improved by ADSC cotransplantation ( P < 0.001, P < 0.001). In the renal subcapsular model, close proximity between hepatocytes and ADSCs was necessary to exert this effect. Unexpectedly, ≈50% of transplanted hepatocytes were attached by ADSCs in the liver. In an in vitro study, the hepatocyte function was significantly improved by ADSC coculture supernatant ( P < 0.001). The multiplex assay and inhibition test demonstrated that hepatocyte growth factor, vascular endothelial growth factor, and interleukin-6 may be key factors for the abovementioned effects of ADSCs. Conclusions: The present study revealed that ADSC cotransplantation can improve the engraftment of transplanted hepatocytes. This effect may be based on crucial factors, such as hepatocyte growth factor, vascular endothelial growth factor, and interleukin-6, which are secreted by ADSCs.